(untitled) (Kairaranga, 2024)
It is with deep sorrow that we at Kairaranga remember Professor Angus Hikairo Macfarlane (Ngāti Whakaue, Te Arawa) CNZM, FRSNZ, a visionary educator and respected colleague. Professor Macfarlane’s contributions to the field of education are significant and enduring. His legacy includes not only his well-known educational models such as the ‘Educultural Wheel’, the Hikairo Schema, the Mana Model, and He Awa Whiria, but also his deep commitment to equity, his belief in the importance of manaakitanga and whanaungatanga and his generosity of spirit. Perhaps lesser known is the very significant contribution that Professor Angus Macfarlane has made to the journal Kairaranga. Professor Macfarlane was instrumental in the development of the journal, and was there at its inception when four RTLB who were engaged in the original RTLB training programme got together to discuss how they might provide a platform for RTLB to share their research and practice. These four were Cath Steeghs, Carol Watts, Paul Mitchell, and Grant Ackerman. A fifth RLTB was to join soon after, Graeme Nobilo. At this time, Professor Angus Macfarlane was approached for support and guidance, and he quickly saw the value of what was being proposed.